Mode I interlaminar fracture toughness of additively manufactured carbon fibre thermoplastic - Goh, Guo Dong (2018)
Mode I interlaminar fracture toughness was investigated for the first time for continuous carbon fiber reinforced nylon thermoplastics fabricated using fused filament fabrication (FFF). To illustrate the effect of process temperature on the fracture toughness of the FFF-fabricated continuous carbon FRP composite, the nozzle temperature, bed temperature, and printing speed of the laminate were varied. Mode I interlaminar fracture toughness was evaluated by a standard double cantilever beam (DCB) test. The experimental result shows that Mode I interlaminar fracture toughness increases with increase nozzle and bed temperatures and decreases with printing speed. The decrease in the interlaminar properties was discussed on the basis of fractographic observation derived from optical microscope.